The Entangled Nature of First Language Learning, Education, and Literacy - Tan Arda Gedik (Cadernos de Linguística)
The entangled relationship between first language acquisition, education, and literacy challenges conventional linguistic paradigms. This paper explores recent findings revealing the intricate interplay of these factors, particularly emphasizing the impact of education and literacy on grammatical knowledge. Drawing on studies conducted in diverse linguistic contexts, this paper argues against the universal applicability of conventional metrics such as the High Academic Attainment/Low Academic Attainment (HAA/LAA) cut-off to investigate the role of reading, advocating for a more nuanced understanding of linguistic development that considers local educational dynamics. Additionally, the paper discusses methodological challenges in studying illiterate populations and proposes alternative measures to capture the cumulative effects of language experience. Ultimately, the paper underscores the importance of interdisciplinary collaboration in developing inclusive research methodologies and educational interventions that address the diverse needs of learners worldwide. By embracing the complexities of language learning, education, and literacy, linguists can advance our understanding of human language capabilities and promote more equitable opportunities for linguistic development.